2020
DOI: 10.1080/10584609.2020.1784328
|View full text |Cite
|
Sign up to set email alerts
|

Why Don’t We Learn from Social Media? Studying Effects of and Mechanisms behind Social Media News Use on General Surveillance Political Knowledge

Abstract: Does exposure to news affect what people know about politics? This old question attracted new scholarly interest as the political information environment is changing rapidly. In particular, since citizens have new channels at their disposal, such as Twitter and Facebook, which increasingly complement or even replace traditional channels of information. This study investigates to what extent citizens have knowledge about daily politics and to what extent news on social media can provide this knowledge. It does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 46 publications
3
46
1
4
Order By: Relevance
“…Studies linking web-tracking and survey data showed increased learning about politics [99], but also a turning away from important topics [100], whereas other experiments demonstrated an overall beneficial effect of digital media on issue salience [101]. These findings, however, stand in contrast to fewer, yet several other studies that find a detrimental association between political knowledge and digital media use [102][103][104][105][106].…”
Section: Few Articles Have Shed Light On Causal Effects Between Social Media Use and Trust A Field Experiments In The Unitedmentioning
confidence: 94%
“…Studies linking web-tracking and survey data showed increased learning about politics [99], but also a turning away from important topics [100], whereas other experiments demonstrated an overall beneficial effect of digital media on issue salience [101]. These findings, however, stand in contrast to fewer, yet several other studies that find a detrimental association between political knowledge and digital media use [102][103][104][105][106].…”
Section: Few Articles Have Shed Light On Causal Effects Between Social Media Use and Trust A Field Experiments In The Unitedmentioning
confidence: 94%
“…Shehata and Strömbäck (2021), for example, conducted a longitudinal survey in Sweden and found that using social media for news, in contrast to online news websites and more traditional outlets, has null effects on political learning. Several other studies in different contexts have confirmed that people usually learn very little about political or societal relevant issues by following social media platforms like Facebook (Boukes 2019;Lee and Xenos 2019;van Erkel and Van Aelst 2020). Scholars have suggested multiple explanations for these findings, from the more personalized and one-sided streams of news to information overloads or simply a lack of relevant factual information on social media.…”
Section: News Use and Political Knowledgementioning
confidence: 99%
“…Lee, , 2020Shehata & Strömbäck, 2018;van Erkel & Van Aelst, 2020). Such adverse pattern was consistent across crosssectional survey data (Cacciatore et al, 2018) and longitudinal survey data (S. Lee, 2020;van Erkel & Van Aelst, 2020)-and in various countries, such as the United States (S. Lee & Xenos, 2019;Oeldorf-Hirsch, 2018), Sweden (Shehata & Strömbäck, 2018), Belgium (van Erkel & Van Aelst, 2020), and Korea (S. Lee, 2019).…”
Section: Social Media Knowledge and Miscalibrationmentioning
confidence: 63%